E0161 Establishment of minipig model of ischaemic heart failure with acute myocardial infarction by coronary occlusion with balloon occluding and intermixture injecting of microthrombi and plastic microspheres. (17th November 2010) - Zhang, Jing; Fu, Xianghua; Wang, Qingsheng; Fan, Xinna; Wang, Xuechao; Wang, Yanbo
Abstract : Objective: To evaluate the of method of minipig model of ischaemic heart failure (HF) with acute myocardial infarction (AMI) by coronary occlusion with balloon occluding and coadministration injecting of microthrombi and plastic microspheres. Methods: A total of 18 minipigs were selected. After coronary angiography, angioplasty balloons were placed in the mid-distal of left anterior descending (LAD). The balloon was inflated intermittently to occlude the LAD 3 times and then occlude contineously for 120 min. After the balloon was taken out, 4F judkins angiogrphic catheter was superelectively engaged in LAD and 3 ml intermixture of microthrombi and plastic microspheres were injected at 10 min interval until TIMI myocardial perfusion grade<2 and left ventricular end-diastolic pressure maintaining from 15 to 18 mm Hg. Electrocardiography (ECG), haemodynamic perameters, ultrasonic cardiogram, cTnI and CK-MB were measured. Myocardiol infarcted area was evaluated with pathologic examination. Results: 14 days later, 15 minipigs survived and fourteen satisfied the criteria (pulmonary capillary wedge pressure, PCWP>18 mm Hg and cardio output, CO decreased beyond 30%). The change of ECG, haemodynamic perameters, CKMB, cTnI and cardiac pathologic examination were in accordance with AMI. Occlusion A stable experimental method of minipig model of ischaemic heart failure (HF) with acute myocardial infarction (AMI) by coronary occlusion with balloon occluding and coadministration injecting of microthrombi and plastic microspheres was established. The method had advantages of closed chest, higher succeed rate and stablility to those of drug induced, tachycardia-pacing induced, coronary artery ligation induced or microsphere injection alone.